(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the importance of developing pedagogical skills in the process of teaching the English language. English plays a key role not only as a tool for learning the language but also in developing students’ communication, expression of ideas, and necessary pedagogical skills in the educational process. The article highlights the impact of the English language on the teaching and learning process in the education system, interactive methods, and ways of creating effective communication among students. The role of English in developing pedagogical skills is crucial for enhancing the efficiency of the educational process. Through learning the language, students acquire independent thinking, writing, and oral communication skills. The article analyzes methods for developing critical thinking, problem-solving, and active participation in social environments through English language teaching. Interactive activities, group work, and discussions encourage students to engage more actively in learning English. This article explains the role and significance of the English language in the development of pedagogical skills, highlighting the importance of its effective use in the educational system. The methodological and psychological approaches of teaching English help in developing pedagogical skills, enabling students not only to learn the language but also to achieve success in the broader educational system.